El Excentrico, 1960-08-20 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
August 20, 1960 [20 de Agosto de 1960]. Ano 10, No 22. Cover has a photograph of professional swimmers, Lynn Burke, Ann Warner, Carolyn Wood, and Chris Von Saltza. They would be representing the United States in the swimming event in the 1960s Olympics.